2020
DOI: 10.3390/ma13235470
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation and Experimental Investigation of the Preparation of Aluminium Alloy 2A50 Semi-Solid Billet by Electromagnetic Stirring

Abstract: Electromagnetic stirring (EMS) has become one of the most important branches of the electromagnetic processing of materials. However, a deep understanding of the influence of the EMS on the thermo-fluid flow of the aluminium alloy melt, and consequently the refinement of the microstructure is still not available. This paper investigated the influence of the operating parameters of EMS on the magnetohydrodynamics, temperature field, flow field, and the vortex-shaped structure of the melt as well as the microstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…The specific heat capacity C str and the thermal conductivity λ str of the strips actually change with the temperature during SSPR and are not constant values. At present, the thermal and elastic property coefficient used in thermal formation simulations is mostly invariant, resulting in certain errors between the experimental and simulated values [21][22][23]. Thus, the coefficients varying with temperature are necessary in SSPR simulation.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…The specific heat capacity C str and the thermal conductivity λ str of the strips actually change with the temperature during SSPR and are not constant values. At present, the thermal and elastic property coefficient used in thermal formation simulations is mostly invariant, resulting in certain errors between the experimental and simulated values [21][22][23]. Thus, the coefficients varying with temperature are necessary in SSPR simulation.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Numerous studies have shown that the use of electromagnetic stirring (EMS) in DC processes can solve the aforementioned problems [12,13]. Electromagnetic continuous casting technology has always been a very attractive method in aluminum alloy production.…”
Section: Introductionmentioning
confidence: 99%
“…The behaviors of heat and mass transfer at the solid-liquid interface are essential factors during the continuous casting, which affects the quality of final product. With the rapid development of continuous casting in recent years, the electromagnetic stirring (EMS) can transfer heat and kinetic energy without direct contact with molten steel, which is widely used in continuous casting, [1][2][3][4][5][6][7] semisolid casting, [8] and directional solidification processes. Due to the effect of EMS on improving the solidification structure of billet, reducing the superheat of molten steel, and reducing the defects of center segregation [9,10] and porosity, [11] it has been widely concerned and studied by researchers.…”
Section: Introductionmentioning
confidence: 99%